Infantile cardiac hemangioma causing right ventricular inflow obstruction. (September 2019) - Karunasumetta, Chananya; Wongbhuddha, Chawalit; Sangkhamanon, Sakkarn; Mokarat, Bundit
Cardiac hemangiomas are extremely rare tumors, especially in infants. We present the case of a 4-month-old girl who developed cyanosis due to a large right atrial tumor causing right ventricular inflow obstruction. The patient underwent emergency surgery for tumor resection and recovered uneventfully. Pathological examination confirmed the diagnosis of a combined capillary and cavernous type hemangioma.